2019
DOI: 10.1007/s00402-019-03155-1
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal resistance profiles in deep infection following primary hip and knee arthroplasty: a study using the NJR dataset

Abstract: Introduction This study aimed to (1) report the rates of resistance against a variety of antibiotics for pure Staphylococcal infections, and (2) examine the impact of ALBC use at primary surgery has on resistance patterns for patients undergoing first-time revision of primary hip and knee arthroplasty for indication of infection. Materials and methods Data from the National Joint Registry database for England and Wales were linked to microbiology data held by Public Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Hansen et al 39 did not find a change in antibiotic resistance patterns after the introduction of routine ALBC in primary TKA. Data from the National Joint Registry, however, have shown that the use of gentamicin‐loaded bone cement in primary TKA and THA increases the risk of gentamicin resistance and methicillin resistance at the time of revision for subsequent PJI 40 . Further studies are warranted to assess the consequences of antibiotic resistance in the setting of ALBC use in primary joint replacement.…”
Section: Resultsmentioning
confidence: 99%
“…Hansen et al 39 did not find a change in antibiotic resistance patterns after the introduction of routine ALBC in primary TKA. Data from the National Joint Registry, however, have shown that the use of gentamicin‐loaded bone cement in primary TKA and THA increases the risk of gentamicin resistance and methicillin resistance at the time of revision for subsequent PJI 40 . Further studies are warranted to assess the consequences of antibiotic resistance in the setting of ALBC use in primary joint replacement.…”
Section: Resultsmentioning
confidence: 99%
“…It was therefore advocated to be suspicious of a possible gentamicin resistance in septic revision situations and better combine 2 antibiotics in the spacer/revision cement. 21,22 Of most clinical importance was the recent finding that bacteria found in PJI -even if resistant to gentamicin -did not show cross-resistancies to other antibiotics commonly used for antibiotic treatment. 23 Resistance patterns in Nordic countries…”
Section: Albc Use and Antimicrobial Resistance Developmentmentioning
confidence: 99%
“…The occurrence of infection not only leads to the failure of the implant and the surgery but also increases the patients’ recovery period and makes an economic burden on both patients and the medical system. The use of antibiotics is a common and effective way to control this issue, but it also has some disadvantages ( Klein et al, 2016 ; Holleyman et al, 2019 ). Bacterial infection on the surface of the implanted material may eventually form a biofilm and reduce or completely inhibit the beneficial effects of the bactericidal drugs.…”
Section: Introductionmentioning
confidence: 99%